Literature Map on the Effect of Education on Entrepreneurial Intention at an Early Age: A Bibliometric Review - Loso Judijanto; Rosdiana Arief Tang; Hubaenah Hubaenah (West Science Journal Economic and Entrepreneurship, 2025)
The increasing emphasis on entrepreneurship education as a means to stimulate entrepreneurial intention from an early age has generated a significant body of academic literature across diverse disciplines. This study presents a bibliometric review aimed at mapping the intellectual structure, thematic evolution, and global research trends related to the effect of education on entrepreneurial intention among young learners. Using data retrieved from the Scopus database and analyzed via VOSviewer, a total of relevant publications from 2000 to 2025 were examined through co-authorship, country collaboration, and keyword co-occurrence analyses. The findings reveal that the research field is dominated by theoretical frameworks such as the Theory of Planned Behavior, with core contributions from scholars like Ajzen, Krueger, Liñán, and Fayolle. Central themes include entrepreneurial education, intention, mindset, and creativity, while recent studies increasingly address sustainability, social entrepreneurship, and curricular innovation. Geographical analysis shows strong contributions from Malaysia, China, the United States, and several European countries, with collaborative networks forming across regions. The temporal keyword overlay further highlights the transition from foundational behavioral research to applied and values-driven themes in recent years. Despite the field’s maturity, research gaps remain, including the lack of longitudinal data, limited cultural diversity, and minimal integration of informal or digital learning environments. This study provides valuable insights for researchers, educators, and policymakers seeking to advance the design and implementation of impactful entrepreneurship education programs aimed at nurturing future entrepreneurs from early developmental stages.